Neonatal outcomes of eclamptic mothers in a tertiary government rural teaching hospital of Eastern India - Bandyopadhyay, Santanu; Das, Rajib; Burman, Medhatithi; Datta, Asok Kumar (Indian Journal of Child Health, 2019)
Background: Studies related to the neonatal outcomes of eclamptic mothers in a rural sociodemographic setting of India are not abundant. Objective: The objective of the study was to identify and assess the significance of the neonatal outcomes of eclamptic mothers in a rural population. Materials and Methods: This was a prospective, cross-sectional, observational, and epidemiological study in a tertiary care government teaching hospital catering rural agro-based population of Eastern India. The study was conducted during April 2012–March 2013 and consisted of two groups. One group comprised neonates born to 100 consecutive eclamptic mothers and another consisted of neonates of 100 non-eclamptic (control) mothers. Both groups were statistically matched after selection through inclusion-exclusion criteria. Results: The majority of eclamptic mothers were unbooked, primigravidae (86%), in late teens (66%), belonging to socioeconomic Class IV (92%) of modified Kuppuswamy scale (2007). About 72% of neonates were born with one or more adverse neonatal outcomes (p